Feedback Quantization for Linear Precoded Spatial Multiplexing. (29th January 2008) - Simon Simon, Claude Claude; Leus Leus, Geert Geert
Abstract : This paper gives an overview and a comparison of recent feedback quantization schemes for linear precoded spatial multiplexing systems. In addition, feedback compression methods are presented that exploit the time correlation of the channel. These methods can be roughly divided into two classes. The first class tries to minimize the data rate on the feedback link while keeping the performance constant. This class is novel and relies on entropy coding. The second class tries to optimize the performance while using the maximal data rate on the feedback link. This class is presented within the well-developed framework of finite-state vector quantization. Within this class, existing as well as novel methods are presented and compared.